PENGGUNAAN LOGIKA FUZZY MAMDANI UNTUK MENGETAHUI KEPUASAN MAHASISWA TERHADAP PELAYANAN TENAGA KEPENDIDIKAN - Amrul Hinung Prihamayu (LPPM Unbaja, 2023)
At the FEBI IAIN Ponorogo, the educational staff consists of finance, academic, library, and laboratory departments. Evaluation of educational staff is carried out at the end of each semester. Evaluation is carried out by distributing questionnaires through Google Forms, with respondents being active students, Ekonomi Syariah, Perbankan Syariah and Manajemen Zakat dan Wakaf. From the evaluation that was carried out, several different types of data were obtained; for example, the first respondent stated that the service of education personnel was good enough for students, while the second respondent stated that there was a need for improvement in providing an active, fast, and responsive response from education staff to students. Based on the two samples of respondents' answers, there are differences in the satisfaction felt by students as consumers. To analyze these differences in satisfaction, a method is needed to get the final result of satisfaction. Fuzzy logic is a method that can be used to analyze data based on the uncertainty of human judgment. This can be inferred from the research conducted. The level of satisfaction, especially the level of service satisfaction, can be determined using Mamdani fuzzy logic.